Internalizing Psychiatric Comorbidities Among Adolescents with Anorexia Nervosa - Fiacco, G.; Catone, G.; Salerno, F.; Gritti, A.; Gleijeses, M.G.; Carotenuto, M. (International Journal of Pediatrics and Child Health, 2024)
Anorexia Nervosa (AN) is a multifactorial psychiatric disorder classified among eating and feeding disorders and frequently associated with psychiatric comorbidities, particularly among adolescents. The main objective of the study was evaluating the psychiatric comorbidities associated with AN, analyzing how these conditions influence each other, triggering challenges in clinical management. The study was conducted at the Child Neuropsychiatry Unit Clinic at Vanvitelli University and involved 60 AN inpatients. Retrospective data collection was obtained through analysis of several psychodiagnostic tests. The EAT-26 (Eating Attitude Test) was administered to assess the presence of dysfunctional eating behaviors, while the BUT (Body Uneasiness Test) was used to identify potential signs of body dysmorphic disorder. The SCARED (Screen for Child Anxiety Related Disorders) and CDI (Children’s Depression Inventory) were employed to investigate the presence of anxious and depressive symptoms. The WISC-IV (Wechsler Intelligence Scale for Children – Fourth Edition) was used to measure intellectual quotient and exclude the presence of intellectual disability. In addition, BMI at discharge of patients was evaluated as an outcome measure for treatment. Results highlight a significant relationship between AN and psychiatric comorbidities, providing important insights for a deeper understanding of the psychiatric dynamics associated with AN. Pearson correlation analysis revealed a strong positive correlation between the scores of the Eating Attitude Test (EAT-26) and the Body Uneasiness Test (BUT) (r=0.730; p<0.001), suggesting that subjects with dysfunctional eating behaviors tend to exhibit high dissatisfaction with their body image. A moderate correlation between the EAT and the SCARED (Screen for Child Anxiety Related Emotional Disorders) (r=0.505; p<0.001) indicates that eating disorders are associated with elevated anxiety levels, while the EAT showed a moderate correlation with the Children’s Depression Inventory (CDI) (r=0.411; p=0.001), suggesting a relationship between dysfunctional eating behaviors and depressive symptoms. Furthermore, the data show a significant increase in BMI during hospitalization, highlighting the importance of targeted therapeutic interventions. These findings contribute to enhancing diagnostic and therapeutic strategies in the management of patients with AN.